Pengaruh Return On Assets, Net Profit Margin, Dan PROPER Terhadap Price To Book Value Dimoderasi Corporate Social Responsibility - Saitio, Jose Aldo; Putra, Angga Sanita (Jurnal Ilmiah Wahana Pendidikan, 2025)
Global competition and world phenomena force companies to continue to grow. To be able to maintain survival in the midst of these conditions, every company needs to increase its value. In an effort to increase its value, understanding the factors that can affect the value of the company such as financial, environmental, and social is very important. This study aims to determine, analyze, and describe the effect of Return on Assets, Net Profit Margin, and PROPER on Price to Book Value, and consider Corporate Social Responsibility as a moderating variable. This study uses quantitative methods with descriptive and verification approaches. The population of this study are manufacturing companies in the automobiles & spare parts, household goods, and apparel & luxury goods subsectors listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022, totaling 37 companies. Determination of the sample using purposive sampling technique with the final sample size is 10 companies. The data analysis method used is multiple linear regression analysis and MRA (Moderated Regression Analysis) analysis with the help of Statistical Product and Service Solutions software (IBM SPSS 25). The results of this study indicate that (1) Return on Assets partially has no effect on Price to Book Value, (2) Net Profit Margin partially affects Price to Book Value, (3) PROPER partially affects Price to Book Value, (4) Corporate Social Responsibility cannot moderate the relationship of Return on Assets to Price to Book Value, (5) Corporate Social Responsibility cannot moderate the relationship of Net Profit Margin to Price to Book Value, (6) Corporate Social Responsibility can moderate the relationship of PROPER to Price to Book Value.